Simbolisme Kijang Muncak (Muntiacus muntjak) pada Relief Karmawibhangga Candi Borobudur: Studi Etnozoologi dan Relevansinya Terhadap Pendidikan Karakter - Izma Fatimatul Azizah; Setiyo Prajoko; Serafica Btari Christiyani Kusumaningrum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to identify and analyze the symbolism of the muntjac deer depicted in the Karmawibhangga Relief at Borobudur Temple through an ethnozoological approach and its relevance to character education values. The method used was a qualitative descriptive approach with an ethnographic design. Data were collected through observation, interviews, literature study, and documentation, and analyzed descriptively. The results indicate that five muntjac deer individuals are depicted across three panels, namely panels 93, 105, and 109. Morphometric analysis shows a high level of proportional similarity between the relief depiction and the real-life muntjac deer. The symbolism of the muntjac deer in the relief represents ahimsa, gentleness, and ecological background markers. In conclusion, the presence of the muntjac deer in the Karmawibhangga Relief holds symbolic meanings that are relevant to character education values, particularly peace-loving and responsibility. Keywords: Borobudur Temple, Ethnozoology, Indian Muntjac, Character Education, Karmawibhangga Relief